A pilot study: Comparing a novel noninvasive measure of cerebrovascular stability index with an invasive measure of cerebral autoregulation in neonates with congenital heart disease - Carlin A. Merkel; Kenneth M. Brady; Jodie K. Votava-Smith; Nhu N. Tran (Journal of Clinical and Translational Science, 2023)
Infants with congenital heart disease (CHD) may have impaired cerebral autoregulation (CA) associated with cerebral fractional tissue oxygen extraction (FTOE). We conducted a pilot study in nine CHD neonates to validate a noninvasive CA measure, cerebrovascular stability index (CSI), by eliciting responses to postural tilts. We compared CSI to an invasive measure of CA and to FTOE collected during tilts (FTOESpot). FTOESpot correlated with CSI, as did the change in FTOE during tilts, but CSI’s correlation with impaired CA did not reach significance. Larger trials are indicated to validate CSI, allowing for noninvasive CA measurements and measurements in outpatient settings.